ChemInform Abstract: Isothermal Section of the Ternary Phase Diagram U—Fe—Ge at 900 °C and Its New Intermetallic Phases. Issue 29 (July 2015) - Henriques, M. S; Berthebaud, D.; Lignie, A.; El Sayah, Z.; Moussa, C.; Tougait, O.; Havela, L.; Goncalves, A. P.
Abstract The isothermal section at 900 °C of the phase diagram of the U—Fe—Ge ternary system is investigated by melting and annealing the elements for 4 weeks prior to quenching in H2O.